Hermeneutics as rigorous science according to Emilio Betti (1890-1968) (2011)
Preheideggerian hermeneutics has often seen as an attempt to develop a methodology of the human sciences. If this project goes back to the later XIXth century, this hermeneutic methodology of the human sciences was carried through for the first time after